2012
DOI: 10.1542/peds.2011-2806
|View full text |Cite
|
Sign up to set email alerts
|

Early Vaccinations Are Not Risk Factors for Celiac Disease

Abstract: OBJECTIVES: To investigate if changes in the national Swedish vaccination program coincided with changes in the celiac disease (CD) incidence rate in infants (ie, the Swedish CD Epidemic), and to assess the potential association between these vaccinations and CD risk. METHODS: All studies were based on the National Swedish Childhood Celiac Disease Register. Using an ecological approach, we plotted changes over time in the nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Similarly to antibiotics and early infections, early vaccinations also influence the immune system. We have previously shown that BCG vaccination is associated with a protective effect for celiac disease, although this has to be interpreted with caution [40]. Adjusting the association between early infections and celiac disease for BCG vaccination status did not affect the association (data not shown).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Similarly to antibiotics and early infections, early vaccinations also influence the immune system. We have previously shown that BCG vaccination is associated with a protective effect for celiac disease, although this has to be interpreted with caution [40]. Adjusting the association between early infections and celiac disease for BCG vaccination status did not affect the association (data not shown).…”
Section: Discussionmentioning
confidence: 86%
“…Adjusting the association between early infections and celiac disease for BCG vaccination status did not affect the association (data not shown). Other vaccinations within the Swedish national program were not risk factors [40]. …”
Section: Discussionmentioning
confidence: 99%
“…Vaccinations, due to modulation of immunity, have been proposed to be involved in the process of developing autoimmune diseases [57] . Scarce data available with regards to CD fail to support this hypothesis [58] .…”
Section: Other Environmental Factorsmentioning
confidence: 99%
“…However a recent study from Sweden [32] found no association between childhood immunizations and CD, and rotavirus immunizations have not yet been included in the general childhood immunization program in Sweden. Hence, biased immunization coverage in CD children is unlikely to explain our results.…”
Section: Discussionmentioning
confidence: 99%